(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Ovarian cancer is the second most common cause of death among gynecological cancer patients in Kenya, and the number of cases is predicted to rise from 1,130 to 2,600 per year by 2040. However, there is very limited diagnostic and treatment capacity. This study aims to establish the first- ever patient experience evidence base of women with ovarian cancer in Kenya and identify challenges and opportunities to improve survival and quality of life. Methods: This was a prospective cross-sectional observational study in which all eligible women attending Moi Teaching and Referral and Aga Khan Hospitals with a diagnosis of ovarian cancer within the previous five years were recruited. Results: Of 104 eligible women with a median age of 51 years, epithelial ovarian cancers were the most common (70%), particularly high-grade serous carcinoma (46%). Most respondents (66%) had advanced disease. Approximately 24% had to travel for five hours or more to access care. The mean average time from experiencing symptoms to diagnosis was 7.4 months. Almost half had never heard of ovarian cancer. Approximately 81% reported that their finances had been affected largely by the diagnosis, with 55% of these women reporting that their household income had dropped below what they needed to survive. Conclusion: The inaccessibility of quality cancer care in Kenya leads to delays in diagnosis and treatment initiation. Innovative awareness strategies, health provider education, and cost mitigation are needed to ensure that women can seek help promptly to reduce morbidity and mortality.